Erosive potential of sugar-free hard candies dissolved in water and artificial saliva - Maria Mercês Aquino Gouveia Farias; Magatha Marquetti Lazzaris de Oliveira; Beatriz Helena Eger Schmitt; Eliane Garcia da Silveira; Silvana Marchiori de Araújo (Universidade Estadual de Campinas, 2016)
Aim: To compare the acidity of sugar-free hard candies dissolved in water and artificial saliva. Methods: Sugar-free Flopi Florestal hard candies (grape, strawberry, cherry, orange, ginger, lemon balm, fennel) were selected and grouped in 2 groups: G-1 (candies dissolved in distilled water) and G-2 (candies dissolved in artificial saliva). Candies were triturated with a porcelain pestle, yielding two samples of 20 g. Samples were dissolved in 120 mL distilled water (G-1) and 120 mL artificial saliva (20 mM NaHCO3, 3 mM NaH2PO4.H2O and 1 mM CaCl2.2H2O) (G-2), obtaining three samples of 30 mL for each of the flavors and groups. pH was measured using potentiometer and combined glass electrode. Titratable acidity was evaluated by adding 100 μL 1M NaOH aliquots until reaching pH 5.5. For statistical analysis, analysis of variance (ANOVA) was used. Means were compared by the Tukey test at 5% significance level (p<0.05) Results: All flavors of G-1 showed pH values below 5.5. Comparison of groups in the same flavor showed a significant increase in pH in flavors of G-2. Comparison of the titratable acidity between G-1 and G-2, showed that fruit flavors were significantly different from each other, with reduced acidity in G-2. Conclusions: All evaluated candies are acid, and dilution in artificial saliva raised their pH and lowered their titratable acidity, reducing their erosive potential.